Public bank lending in Africa in times of crisis - (:unkn) unknown (My University, 2023)
This paper examines State-owned bank lending in Africa in times of crisis. We exploit a sample of 112 banks, including 24 State-owned banks, operating in 8 West African countries over the period 2000–2019. We focus on how bank ownership affects lending, during and after crises. Results indicate that, contrary to domestic-private banks, public banks continue to lend at the same rate during and slightly increase their lending after a crisis. The main explanation of the previous finding is the stability of State-owned bank resources. Finally, the countercyclicality of public banks does not affect their profitability or portfolio quality.
Keywords: African Research